2022
DOI: 10.1172/jci.insight.159093
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell RNA-Seq of human esophageal epithelium in homeostasis and allergic inflammation

Abstract: Inflammation of the esophageal epithelium is a hallmark of eosinophilic esophagitis (EoE), an emerging chronic allergic disease. Herein, we probed human esophageal epithelial cells at single-cell resolution during homeostasis and EoE. During allergic inflammation, the epithelial differentiation program was blocked, leading to loss of KRT6 hi differentiated populations and expansion of TOP2 hi proliferating, DSP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
54
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(57 citation statements)
references
References 60 publications
3
54
0
Order By: Relevance
“…As such, it will be of interest to determine how EoE inflammation impacts the expression of ATP1B3. A recent human scRNA-Seq study identified an increase in proliferating suprabasal cells, but not proliferating basal cells, in the epithelium of active EoE subjects (45). Identification of proliferating cells in the noted human EoE dataset was based on expression of the proliferation marker TOP2A (45).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As such, it will be of interest to determine how EoE inflammation impacts the expression of ATP1B3. A recent human scRNA-Seq study identified an increase in proliferating suprabasal cells, but not proliferating basal cells, in the epithelium of active EoE subjects (45). Identification of proliferating cells in the noted human EoE dataset was based on expression of the proliferation marker TOP2A (45).…”
Section: Discussionmentioning
confidence: 99%
“…A recent human scRNA-Seq study identified an increase in proliferating suprabasal cells, but not proliferating basal cells, in the epithelium of active EoE subjects (45). Identification of proliferating cells in the noted human EoE dataset was based on expression of the proliferation marker TOP2A (45). Although we did not evaluate Top2a , analysis of cell cycle genes in our dataset does not support proliferation across the EoE-enriched suprabasal populations and pathway analysis in these clusters predicted an association with senescence pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with EoE-associated alterations in cell cycle within esophageal keratinocytes, a recent human scRNA-Seq study identified an increase in proliferating suprabasal cells, but not proliferating basal cells, in the epithelium of active EoE subjects ( 42 ). Identification of proliferating cells in the noted human EoE dataset was based on expression of the proliferation marker TOP2A ( 42 ). Interestingly, Top2a expression is highly upregulated in the EoE-enriched murine population suprabasal 5 in our dataset ( Figure 1D ) which further displays enrichment of genes associated with G2/M phase of the cell cycle ( Figure 4C ).…”
Section: Discussionmentioning
confidence: 75%
“…Thus, it is further possible that cells located in the basal cell layer of mice with EoE take on features of the suprabasal cell compartment (Figure 8), including exit from the cell cycle. Consistent with EoE-associated alterations in cell cycle within esophageal keratinocytes, a recent human scRNA-Seq study identified an increase in proliferating suprabasal cells, but not proliferating basal cells, in the epithelium of active EoE subjects (42). Identification of proliferating cells in the noted human EoE dataset was based on expression of the proliferation marker TOP2A (42).…”
Section: Discussionmentioning
confidence: 87%
“…Since its inception in 2019, it has demonstrated its utility at the local laboratory level and beyond such as by generating interest from collaborators in academia and industry. At least 12 publications have already been facilitated by EGIDExpress 15, 16, 17, 18, 19,20, 21, 14, 22, 23, 24, 25 . Datasets will continue to be added to EGIDExpress as they are generated, and we remain flexible to adding new data formats or modes of visualization as new dataset types arise, and we are open to developing new functionalities within the app.…”
Section: Resultsmentioning
confidence: 99%